Aromatic Constituents from the Leaves of Actinidia arguta with Antioxidant and α-Glucosidase Inhibitory Activity - Jong Hoon Ahn; Se Hwan Ryu; Solip Lee; Sang Won Yeon; Ayman Turk; Yoo Kyong Han; Ki Yong Lee; Bang Yeon Hwang; Mi Kyeong Lee (MDPI AG, 2021)
As the leaf of Actinidia arguta has shown antioxidant activity, a study was conducted to identify the active ingredients. Forty-eight compounds were isolated from the leaves of A. arguta through various chromatographic techniques. Further characterization of the structures on the basis of 1D and 2D NMR and MS data identified several aromatic compounds, including phenylpropanoid derivatives, phenolics, coumarins, flavonoids and lignans. Among them, five compounds were newly reported, naturally occurring, and named argutosides A-D (1-4), which consist of phenylpropanoid glycosides that are conjugated with a phenolic moiety, and argutoside E (5), which is a coumarin glycoside that is conjugated with a phenylpropanoid unit. The isolated compounds showed good antioxidant and α-glucosidase inhibitory activity with differences in activity depending on the structures. Molecular docking analysis demonstrated the interaction between the hydroxyl and carbonyl groups of compounds 1 and 5 with α-glucosidase. Taken together, the leaves of A. arguta are rich in aromatic compounds with diverse structures. Therefore, the leaves of A. arguta and their aromatic components might be beneficial for oxidative stress and glucose-related diseases.